It is not enough: The moderation effect of entrepreneurship education in Mexican University students - Irery L. Melchor-Duran; Sandra Yesenia Pinzon Castro; Alejandro Cheyne-Garcia; Araceli Alvarado-Carrillo (Administrative Sciences, 2024)
Understanding the impact of entrepreneurship education on the entrepreneurial cognition of university students is relevant to finding ways to foster entrepreneurship that boost the economy in developing countries. The objective of this study is to determine the influence of personal attitude, perceived behavioral control, and subjective norms on entrepreneurial intention, and to discover if there exists a moderation effect of entrepreneurship education on the abovementioned aspects. We collected 343 questionnaires of students of the Center for Administrative and Economic Sciences of a Mexican university. We used structural equations through the method of partial minimum squares, and, to test the hypothesis, we used the Smart-PLS 3.0 software. The results indicate that entrepreneurship education does not have a significant moderation effect on the relationship between personal attitude on entrepreneurial intention and perceived behavioral control on entrepreneurial intention. However, there exists a significant and positive influence of personal attitude on entrepreneurial intention and perceived behavioral control on entrepreneurial intention. We conclude that current entrepreneurship education has the opportunity to create impactful outcomes because the theory is easy, but entrepreneurship in reality is hard and requires more effort. We recommend including a wider view with external resources like lectures of experts from the entrepreneurial ecosystem and support from government and potential investors, among other approaches.
Keywords: 350; entrepreneurship education; university students; entrepreneurial intention; moderationeffect; structural equations